2012
DOI: 10.1590/s0102-695x2012005000057
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil from leaves of Lantana camara: a potential source of medicine against leishmaniasis

Abstract: Abstract:Leishmaniasis is an infection of viscera or tegument caused by protozoa Leishmania sp. The extensive period required for the treatment, which involves the use of toxic medicines, leads patients to drop treatment increasing the development of resistant forms of Leishmania sp. Lantana camara L., Verbenaceae, is a tropical plant native from America. Folk uses have been described for treatment of tumors, tetanus, rheumatism and malaria. This study evaluates the leishmanicidal activity of the essential oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…These results corroborate with those reported by Machado et al [28] that found farnesene derivatives as the most representative constituents (22 %) and their bioassays using EO from Lantana camara revealed a significant leishmanicidal activity against L. amazonensis (IC 50 /72 h = 0.25 μg/mL), except for the cytotoxic activity, in which the authors obtained high values on Brine shrimp (CC 50 10 μg/mL). Subsequently, Gawde et al [29] observed that the chemical composition of M. chamomilla was similar to the one found in our study (β-farnesene, α-bisabolol oxide B, chamazulene) but no leishmanicidal activity on L. donavani was observed.…”
Section: Discussionsupporting
confidence: 91%
“…These results corroborate with those reported by Machado et al [28] that found farnesene derivatives as the most representative constituents (22 %) and their bioassays using EO from Lantana camara revealed a significant leishmanicidal activity against L. amazonensis (IC 50 /72 h = 0.25 μg/mL), except for the cytotoxic activity, in which the authors obtained high values on Brine shrimp (CC 50 10 μg/mL). Subsequently, Gawde et al [29] observed that the chemical composition of M. chamomilla was similar to the one found in our study (β-farnesene, α-bisabolol oxide B, chamazulene) but no leishmanicidal activity on L. donavani was observed.…”
Section: Discussionsupporting
confidence: 91%
“…This previous study presented germacrene D, caryophyllene and farnesene as the major compounds. Thus, despite the absence of antimycobacterial activity of EOLC, the described composition of EOLC and EOPE (Dutra et al, 2012a;Machado et al, 2012b) suggests that the germacrene D is not related to the antimycobacterial activity revealed by EOPE in this work, since both essential oils presented germacrene D as one of the major compounds.…”
Section: Bovis Is Often Used As a Model To Investigate M Tuberculmentioning
confidence: 55%
“…The composition of the currently used EOLC was described in a previous study that showed its leishmanicidal potential (Machado et al, 2012b). This previous study presented germacrene D, caryophyllene and farnesene as the major compounds.…”
Section: Bovis Is Often Used As a Model To Investigate M Tuberculmentioning
confidence: 98%
See 1 more Smart Citation
“…The essential oil of its flowers and leaves possess a variety of chemical compounds with leishmanicidal, antimicrobial, anticancer, antiulcer, anti-inflammatory activities, among others. However, in high doses, these species can be toxic to some animals (Oyourou et al, 2013;Machado et al, 2012;Montanari et al, 2011;Sousa et al, 2011;Costa et al, 2009;Sharma and Kumar, 2009).…”
Section: Introductionmentioning
confidence: 99%